2018
DOI: 10.1007/s00330-018-5376-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced cone-beam breast-CT (CBBCT): clinical performance compared to mammography and MRI

Abstract: • CE-CBBCT diagnostic accuracy (AUC) was comparable to MRI in dense breasts. • CE-CBBCT improved sensitivity and AUC in comparison to MG and NC-CBBCT. • CE-CBBCT has inferior sensitivity but higher specificity than MRI. • CE-CBBCT is a potential imaging alternative for patients with MRI contraindications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
3
47
0
1
Order By: Relevance
“…15 The high resolution, but also the possibility to evaluate the images in different planes, increases and facilitates the characterization of lesions regarding suspicious features such as conspicuity, calcifications, and asymmetries, as well as masses. 14,22,23 Due to the retrospective nature of our study, no mammography was performed in addition to B-CT, and previous mammography was available only in a limited number of cases, thus precluding a systematic 2 1 5555 5 5 4444 3 3 4545 3 3 4444 3 3 2 5555N M N M4455N M N M5545N M N M5444N M N M 3 5555 5 5 4455 4 4 4444 4 4 5544 3 3 4 5555N comparison. Nevertheless, our initial data demonstrate a high B-CT performance in terms of image quality.…”
Section: Discussionmentioning
confidence: 99%
“…15 The high resolution, but also the possibility to evaluate the images in different planes, increases and facilitates the characterization of lesions regarding suspicious features such as conspicuity, calcifications, and asymmetries, as well as masses. 14,22,23 Due to the retrospective nature of our study, no mammography was performed in addition to B-CT, and previous mammography was available only in a limited number of cases, thus precluding a systematic 2 1 5555 5 5 4444 3 3 4545 3 3 4444 3 3 2 5555N M N M4455N M N M5545N M N M5444N M N M 3 5555 5 5 4455 4 4 4444 4 4 5544 3 3 4 5555N comparison. Nevertheless, our initial data demonstrate a high B-CT performance in terms of image quality.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve detection rates, contrast‐enhanced imaging of the breast has been developed. This method is already established in breast MRI 7–10 and is also increasingly used in mammography 11‐22 and breast CT (BCT) 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…When comparing imaging modalities, CE‐CBBCT has been shown to have improved malignancy detection compared with mammograms . Wienbeck, et al have shown that MRI and CE‐CBBCT were more sensitive and accurate compared to noncontrast enhanced studies such as mammogram and NC‐CBBCT, but they are less specific. This suggests CE‐CBBCT may be useful as a screening tool for those who are unable to undergo MRIs.…”
Section: Emerging Technologiesmentioning
confidence: 99%